Bioresources as the tool for Biodiversity Management - Dave Kalpana; Jain Shruti (International Journal of Life Sciences, 2015)
Water management in general takes account of biodiversity and conservation aspects, but further some protective measures are needed. Cost of water management directly or indirectly influences the aquatic ecosystem. Biotic and abiotic factors are both independent and interdependent resources. Multispecies communities like plankton, fishes and macrophytes are bioresources which are essential for the stabilization of ecosystem. Bioindicators and bioresources are both responsible to maintain the food chain of pond ecosystem. Species composition and biomass distribution are important for affecting the transfer of energy in food chain of pond. Phytoplankton represents the base of primary producer in aquatic ecosystem and plays a major role in the global cycling of carbon, nitrogen, phosphorous and other elements; and by this they help in regulation of the earth’s climate. Bioresources are the natural bioindicators of pollution in the water body. Bioindicators are anthropogenically induced which affects biomolecules, their biochemical and physiological parameters that are casually linked to the different levels of biological organisation. Sometimes the reason behind loss of biodiversity is due to competition between bioresources in a limited space. Present investigation is an attempt to study and understand the basic status in hydrobiology and productivity possibility of reservoir.